Chitosan/nano ZnO composite films: Enhanced mechanical, antimicrobial and dielectric properties - P. Mujeeb Rahman; V.M. Abdul Mujeeb; K. Muraleedharan; Steni K. Thomas (Arabian Journal of Chemistry, 2018)
For the first time, unfocused Chitosan nano ZnO composite film was prepared by a simple one pot procedure. The novel composite materials were ably characterized by various physico-chemical methods. Dielectric and conductivity features of composite materials were analysed. The result showed that both dielectric constant and conductivity values were improved when nano ZnO was incorporated. The potential applicability of composite films to perform as an efficient antimicrobial packaging material was evaluated. Antimicrobial analysis showed that all composite films exhibited enhanced antimicrobial efficacy as compared to pure chitosan film and it is linearly related to the amount of ZnO particles in the matrix.